Legitimacy of the limitation on freedom of religion during imprisonment (in the light of polish and international regulations) - Sitarz, Olga; Jaworska-Wieloch, Anna (Law Journal of New Bulgarian University, 2022)
This article is devoted to consider the legitimacy of restrictions on religious freedom during imprisonment, taking into account the nature of the sentence, the importance of religion in human life and in the life of the convict, as well as international and national regulations. The subject of the analysis is the Polish legal system, starting with the Constitution, which guarantees freedom of conscience and religion to everyone, and in particular Polish executive law, which declares respect for religious freedom in prison. It does not mean the guaranteeing unlimited access to religious practices and services, because imprisonment limits many human freedoms, also in such a sensitive area as religious freedom. In the course of the analysis, we considered the legitimacy of restrictions provided by criminal law, taking into account international standards for the protection of human rights and Polish regulations, which guarantee human rights and freedoms.